2020
DOI: 10.1186/s13223-020-00487-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin D deficiency impairs Treg and Breg responses in offspring mice and deteriorates allergic airway inflammation

Abstract: Background Vitamin D (VitD) can regulate immune responses and maternal VitD-deficiency can affect immune responses in the offspring. This study aimed at investigating the effects of maternal VitD-deficiency during pregnancy on Treg and Breg responses in offspring mice with house dust mite (HDM)-induced allergic airway inflammation. Methods Female BALB/c mice were randomized and fed with normal chow or VitD-deficient diet until their offspring weaned. The offspring mice were fed with normal chow and injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“… 39 Low levels of VitD observed in the plasma of newborn mice caused the deterioration of allergic airway inflammation, suggesting that VitD deficiency affected inflammation. 40 It has been demonstrated that VitD deficiency contributes to lung fibrosis, and VitD supplementation combined with anti-fibrotic therapeutics can ameliorate this symptom. 41 , 42 Previous research has frequently shown the anti-inflammatory effects of VitD in some human diseases, implicating VitD as a possible anti-inflammation therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Low levels of VitD observed in the plasma of newborn mice caused the deterioration of allergic airway inflammation, suggesting that VitD deficiency affected inflammation. 40 It has been demonstrated that VitD deficiency contributes to lung fibrosis, and VitD supplementation combined with anti-fibrotic therapeutics can ameliorate this symptom. 41 , 42 Previous research has frequently shown the anti-inflammatory effects of VitD in some human diseases, implicating VitD as a possible anti-inflammation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Here, vitamin D is also important for maintaining healthy gut microbiota and the activation of Tregs [120,121].…”
Section: Intestinal Disorders and Gut Microbiotamentioning
confidence: 99%
“…In addition, it is intriguing that the consumption of raisins is reported to induce beneficial changes in gut microbiota [119]. Here, vitamin D is also important for maintaining healthy gut microbiota and the activation of Tregs [120,121]. High-fat, high-sugar and high-calorie diet causes obesity; without sufficient exercise, people tend to the onset of metabolic syndrome.…”
Section: Intestinal Disorders and Gut Microbiotamentioning
confidence: 99%
“…10 Specific inflammatory T helper 17 (Th17) cells play a crucial role in the pathogenesis of airway inflammation. 11 A regulatory T (Treg) cell response is vital in the inflammation resolution response. 12 The cells undergo terminal differentiation to elicit conflicting functions with Th17 cells to induce inflammation whereas Treg cells inhibit this phenomenon.…”
mentioning
confidence: 99%
“…12 The cells undergo terminal differentiation to elicit conflicting functions with Th17 cells to induce inflammation whereas Treg cells inhibit this phenomenon. 11,13 Therefore, the balance of the Th17/Treg is critical in the inflammatory response to ameliorate lung inflammation by a uniform balance of Th17/Treg. 14,15 A deficiency of vitamin D can impede the downregulation of Th17 cells and the upregulation of Treg cells, thus unbalancing the proportion of Th17/Treg.…”
mentioning
confidence: 99%